The Influence of Social Protests on Issue Salience among Latinos. (September 2014) - Carey, Tony E.; Branton, Regina P.; Martinez-Ebers, Valerie
Much of the protest literature has examined the policy consequences of social protests. Few studies focus on the effect of social protests on public opinion. We examine the impact of the 2006 immigration protests on the saliency of immigration among Latinos. The 2006 Latino National Survey was in the field before and after the protests began, creating a natural experiment. Using these data, we discover protests increased Latinos' perception of undocumented immigration as the most important problem facing Latinos. Furthermore, our analysis shows that the effect of protest was not uniform across the population but rather contingent on individuals' characteristics.